Data foundations for relationships between economic and transport factors with road safetyoutcomes - Hughes, Brett; Newstead, S.; Shafiei, S.; Hopkins, Sandra (Journal of the Australasian College of road Safety, 2014)
Economic conditions and policies affect transport, resulting in road safety consequences. This paper describes theselection, acquisition, description and assessment of available, appropriate and suitable data for research of thistopic. Data on economic, transport, and road safety were collected and subjected to exploratory analysis and basic diagnostic tests, finding it to be generally suitable to support further analysis, with qualifications and limitations. Appropriate,and suitable data were found to support analysis of the relationships between economic and transport factors androad safety outcomes. Simple regression models identified initial, basic relationships between four road safety outcomes and nine economic activity factors reinforcing the importance of these factors as determinants of road safety outcomes.Characteristics of the data dictated more sophisticated analysis is required to produce more reliable results. The data and initial information provides a solid foundation to base further investigations of relationships between economic and transport factors with road safety